The Early Land Plants Today project (ELPT): A community-driven effort and a new partnership with Phytotaxa - Von Konrat, M.; Soderstrom, L.; Hagborg, A. (Phytotaxa, 2014)
There remains a critical need to synthesize the vast amount of nomenclatural, taxonomical and global distributional data for liverworts and hornworts. This is fundamental in the efforts towards developing a working list of all known plant species under the auspices of the Convention on Biological Diversity (CBD). Such a synthesis has far reaching implications and applications, including providing a valuable tool for taxonomists and systematists, analyzing phytogeographic and diversity patterns, aiding in the assessment of floristic and taxonomic knowledge, and identifying geographical gaps in our understanding of the global liverwort and hornwort flora. We here outline and discuss the methodology as part of an international consortium referred to as the Early Land Plants Today (ELPT) project. There are three fundamental components to the project: 1) a worldwide checklist of liverworts and hornworts; 2) regional or local distribution checklists; and 3) the synthesis of the taxonomy, systematics, and nomenclature on a taxonomic group-by-group basis. The latter, in particular, represents the first endeavour of its kind and will appear as a series of forthcoming papers in Phytotaxa, where ELPT collaborates closely with taxonomic specialists validating and verifying nomenclatural and type data, authorities, original citations, as well as auxiliary data associated with specific taxonomic groups. A brief account of the compilation of regional or local checklists is also provided; these also will be published periodically.